The Dynamics of Export and Import Functions in Turkey: Cointegration and Multivariate Granger Causation Analysis - Altintaş, Halil; Türker, Oğuzhan (International Journal of Asian Social Science, 2014)
The study aims to analyze the determinants of foreign trade through the variables of national income, foreign direct investment, real exchange rates, and export and import prices for the period of 1987-2011. The export and import demand functions in Turkey are estimated using unit root test, co-integration analysis, and Granger causality tests. There is one-way short term Granger causal link from foreign income, real exchange rate and export price towards export in the export model. This model is also characterized by the fact that foreign income, foreign direct investment, real exchange rates and export price are the Granger causes of export in the long-run. In the import model, on the other hand, there is Granger causality link from Turkey’s real GDP, foreign direct investment, and real exchange rate towards import in the long-run. In addition, single way causality links have been encountered from foreign direct investment, real exchange rate and import price to import.